Ups and downs of expatriate health sciences students: towards an understanding of experiences, needs, and suggested recommendations in an Emirati university - Ahmed, Fatma Refaat; Awad, Ramadan Ezat; Nassir, Huda M.; Mostafa, Shahd Tarek; Oujan, Batool Ghiath; Mohamed, Basem Ali; Abumukheimar, Loai A. H.; Abraham, Mini Sara; Al-Yateem, Nabeel; Al-tamimi, Muna; Mottershead, Richard; Dias, Jacqueline Maria; et al. (Frontiers in Education, 2025)
AimTo describe the lived experiences of expatriate students enrolled in an academic institution in the UAE and explore suggested improvement strategies to address their challenges.BackgroundExploring the experiences of expatriate students is crucial for three main reasons. First, expatriate students play a key role in the UAE’s sustainable socio-economic development and diversification. Second, cultural differences among expatriate students raise personal, social, and academic challenges, including pedagogical issues concerning teaching and learning styles and effectiveness. Third, given the global importance of internationalization, expatriates’ experiences should be considered an issue of customer satisfaction.MethodA descriptive, qualitative, narrative study using indirect Colaizzi content analysis of 23 expatriate students’ reflections on their experiences and suggested recommendations.ResultsThe consistent themes cited by participants concerning their experiences centered on dormitory-study life balance, socialization and support networks, and navigating financial challenges. They identified areas for improvement in terms of professional, social, peer, and self-support.ConclusionDeveloping an effective support system is essential to ensure a smooth expatriate student experience. The study findings propose suggestions and recommendations that may help in future planning, including maximizing professional support, providing peer tutoring, boosting academic advising and consultation, encouraging student socialization, and guiding self-development as necessary.